Power aware routing using power control in Ad Hoc networks. - Jung, Eun-Sun
A conventional routing protocol selects a path using the shortest number of hops as a routing metric. Is has been proposed that a different routing metric may be useful to achieve energy savings. One such power-aware routing metric is minimizing the aggregate transmission power on a path from a source to a destination. This metric has been used along with a simple power control protocol, which uses the maximum transmission power for RTS and CTS and the minimum necessary transmission power for DATA and ACK. Although this type of power control protocol does not provide spatial reuse it can conserve energy. We will refer to this kind of power control as the BASIC power control protocol. In this paper, we show that a power aware routing, minimizing the total transmission power, with BASIC power control does not save energy, which contradicts previous studies in the literature. The reason is simple and intuitive but it has been entirely overlooked. Using the power aware routing metric, the selected paths can be much longer than the shortest path. In other words, there can be more hops between a source and a destination. Since BASIC power control does not provide spatial reuse, nodes on a path have to share and compete for the channel bandwidth. Therefore, the throughput achieved between a source and a destination can be lower than that of IEEE 802.11 without power control Also, we found that the metric leads to lower data bits delivered per unit of transmission energy. We show that using the shortest number of hops in conjunction with BASIC power control conserves more energy than power aware routing with BASIC power control.
Keywords: Computer Systems Organization; Computer communication networks; Network architecture and design; Wireless communication; Network protocols; Routing protocols; Design; Experimentation; Measurement; Performance